Tests on flexural strength of carbon\ epoxy composite - Seah, Jason Beng Chin. (2013)
An experiment was done to test for the flexural strength of carbon fiber epoxy composites under different strain rates and temperature. The carbon fiber epoxy samples were subjected to 3 point bending under different temperatures and strain rates. The numerical data obtained from the tests were used to plot the graphs showing the behavior of the specimens subjected to same loadings but under different temperatures and strain rates. The graphs plotted from the data showed that the specimens were more brittle and have higher flexural strength under lower temperatures. The specimens became more viscous and flexural strength dropped when subjected to high temperatures. The specimens tend to be more viscous and have lower flexural strength when subjected under lower strain rate.